Pengaruh Besaran Fee Audit dan Independensi Terhadap Kualitas Audit dan Etika Profesi Auditor Sebagai Moderasi - Prabhawanti, Putu Putri; Widhiyani, Ni Luh Sari (E-Jurnal Akuntansi; Vol 24 No 3 (2018)DO - 10.24843/EJA.2018.v24.i03.p23, 2018)
This study is an empirical study to examine the effect of variable audit fee amount and independence to audit quality with professional ethics as a moderation variable. Data collection method used is using questionnaires distributed directly to auditors at Public Accounting Firm (KAP) working in Bali. The population in this study is all auditors who work at Public Accounting Firm in Bali with the total number of auditors as much as 61 people. The number of samples used are 53 auditors with purposive sampling method. The analysis technique used is Moderated Regression Analysis (MRA).Based on the analysis and hypothesis testing, it can be concluded that (1) audit fee has positive effect on audit quality, (2) independence has negative effect on audit quality, (3) professional ethics auditor unable to moderate audit fee fee on audit quality, (4) ) the ethics of the auditor's profession is able to moderate the influence of independence on audit quality. Keywords: audit fee amount, professional auditor ethics, independence, audit quality